Development of Minimum Competency Assessment (AKM)-Based Exercise Books to Improve Students' Literacy and Numeracy Skills at Sdn Janti 02 Sidoarjo - Nuril Nuzulia; Abd Gafur (Madrosatuna: Journal of Islamic Elementary School, 2022)
Develop a Minimum Competency Assessment-Based Exercise Book to Improve Students' Literacy and Numerical Ability at SDN Janti 02 Sidoarjo to provide exciting and creative learning media in a lesson that aims to improve student learning outcomes. This is one of the reasons behind this development research. The study aimed to develop a minimum competency assessment-based exercise book to enhance students' literacy and numeracy skills at SDN Janti 02 Sidoarjo. This research and development method uses the research and development (R&D) type of Borg & Gall. The results of the development were in the form of a "Pintar AKM" exercise book for Grade 5 elementary schools. (1) the results of this research and development meet the valid criteria with the acquisition of validity, material experts get 90.6%, design experts get 89.3%, and learning experts get 94.6%. (2) the results of the trial to assess the attractiveness of the exercise book based on the minimum competency assessment developed for students at SDN Janti 02 Sidoarjo was 91.8%. (3) student learning outcomes have increased, as seen from the pre-test results of 70.8 and post-test scores of 90.4, so it can be said that the minimum competency assessment-based exercise book is appropriate for students to use.